Escalabilidade, gerência e mobilidade para redes mesh de acesso à internet - Duarte, Jairo Lino (2008)
A Mesh network is considered an evolution of IEEE 802.11 type of network, that adds some new benefits, such as greater coverage area by the use of multiple hops, and robustness by the ability to automatically reconfigure its routes. These benefits make possible the development of networks for broadband access at a low cost. Therefore, a mesh network is a good option for initiatives of digital inclusion projects. The Remesh project, which built two access networks, with users from the academic community of UFF, faced several issues related to the areas of scalability, management and mobility. Despite a considerable part of these issues are typical for access networks and wireless networks, in the context of mesh networks, these issues have some peculiar implications. The focus of this work, is related to these issues and their corresponding solutions, for these issues. The main contributions are the investigation of such issues, their implications on mesh networks. The development of tools for management, the identification of a scalability limitation, and the evaluation of a new solution, and the research on mobility issues support over mesh networks.